Addressing inequalities early in life - Kilpi-Jakonen Elina (Adjacent Digital Politics Ltd, 2022)
The trajectory of a human’s life course is by no means determined at birth. Nevertheless, the circumstances a child is born into and events taking place during the early childhood, or even gestation, shape life-course trajectories